The Effects of Integrating Augmented Reality in Learning Chemical Bonding via Inquiry Towards Chemistry Self Efficacy - Lee Kah Ching; Noor Dayana Abd Halim; Nor Farhah Saidin; Nurul Nadwa Zulkifli; Christnalter Bunsu (Universitas Sriwijaya, 2025)
Chemistry is often perceived as a difficult subject due to its complex and abstract concepts. This has led secondary school students to develop a negative attitude towards Chemistry. Technology such as Augmented Reality (AR) has emerged as a supportive learning tool to assist students in better visualising abstract concepts in Chemistry. Therefore, this study was conducted to design a Chemistry lesson based on the Process-Oriented Guided Inquiry Learning (POGIL) approach integrated with AR for learning chemical bonds and to examine its effect on students’ Chemistry self-efficacy. This study employed a quantitative approach using a one-group, pre-test-post-test design. One school was selected by purposive sampling, where fifteen Form 4 students were randomly chosen as the sample of the study. The findings on students’ Chemistry self-efficacy were analysed using descriptive and inferential analysis. The findings showed a significant difference between the pre- and post-test scores after the intervention. Hence, it is proven that the intervention had a positive effect on students’ Chemistry self-efficacy. The positive results of incorporating AR in learning chemical bonds via POGIL have given educators new insight into suitable pedagogical tools and learning strategies to utilise when teaching Chemistry to secondary school students.